Integrating Wordwall in Islamic Religious Education: A Phenomenological Study of Pedagogical Transformation in Indonesian Primary Schools - Adzibah, Salsabila I'tilaful; Mardiah, Desni; Gasmi, Nur Muhammad (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
The integration of digital technology in education has driven pedagogical innovation across various disciplines, including Islamic Religious Education (IRE). This study investigates the lived experiences of primary school IRE teachers in using Wordwall, a web-based interactive learning platform. Employing a descriptive phenomenological approach, the research explores teachers’ motivations, classroom implementations, and perceived impacts on student engagement and understanding. Data were collected through in-depth interviews, classroom observations, and document analyses involving two purposively selected educators from different institutional contexts. The findings reveal three key themes: a shift in teachers’ perceptions toward technology, with increased confidence and digital self-efficacy; the emergence of a more adaptive and creative professional identity; and the transformation of pedagogical practices from conventional content delivery to participatory, game-based learning. Despite notable challenges, such as limited infrastructure and initial unfamiliarity with digital tools, the study underscores Wordwall's role as a catalyst for pedagogical reflection and renewal. These findings suggest that targeted institutional support, including training and peer collaboration, is essential for sustainable digital innovation in IRE. Limitations include the small sample size and localized setting. Future research should expand to diverse educational contexts to further explore scalable models of technology integration in religious instruction.